Pengaruh atraksi, fasilitas dan aksesibilitas terhadap loyalitas pengunjung di Kebun Teh Nglinggo Samigaluh - Primadani, Efi; Amelia, Viona; Nugroho, Dwi Yoso (CV. Kurnia Grup, 2024)
The Special Region of Yogyakarta is a province with various tourist destinations, one of which is Nglinggo Samigaluh Tea Garden which is an agro-tourism area that not only prioritises tea plantations, but is also equipped with education, research and tourist attractions. This study aims to determine the effect of attractions, facilities and accessibility on visitor loyalty at Nglinggo Tea Garden. The study used a quantitative approach with a sample size of 100 respondents and multiple linear regression analysis techniques, T test and F test to answer the hypothesis. The results showed that hypothesis testing is the partial influence of attractions and facilities on visitor loyalty, but there is no partial influence of accessibility on visitor loyalty to Nglinggo Tea Garden. Simultaneously it is known that attractions, facilities and accessibility have a significant effect on the loyalty of visitors to Nglinggo Tea Garden. As for the coefficient of determination (R2) of 57.5% which means that the visitor loyalty variable can be explained by the variables of attractions, facilities and accessibility.